Spatial Integration Level of Housing Complex with the City Structure. Case of Rzeszów - Martyka, Anna Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In many Polish cities, the aspect of integration of urban structures is underestimated and new investments are not properly connected with the city. This article presents the results of a study with the main objective of assessing the level of spatial integration of residential areas. The study was carried out in several stages; it was based on classical and qualitative methods used in urban planning.
Keywords: housing estates; city structure; integration; spatial integration level; Rzeszów; osiedla mieszkaniowe; struktura miasta; integracja; stopień integracji przestrzennej